Kolaborasi Hexahelix dalam Pengembangan Ekosistem Digital Kreatif di Kota Malang - Anisykurlillah, Rosyidatuzzahro (Universitas 17 Agustus 1945 Surabaya, 2023)
Malang City is one of the cities projected to become a digital-based Creative City using the digital creative industry subsector as its leading subsector. The digital creative industry subsector includes applications and games. After the Covid-19 pandemic, Malang City has strengthened its steps to become a digital-based creative city. Developing a creative digital ecosystem in Malang City requires a strategy to achieve post-pandemic goals. The strategy implemented by the Malang City Government in developing an innovative digital ecosystem is through hexahelix collaboration. The hexahelix partnership comprises six components: government, business, academics, community, media, and banking. This research aims to analyze and map the role of each stakeholder involved in the Hexahelix collaboration in developing a creative digital ecosystem in Malang City. The research results show that the Hexahelix collaboration in developing the innovative digital ecosystem in Malang City has not run optimally. The contribution of each element in the hexahelix collaboration needs to be considered to support the successful development of the creative digital ecosystem in Malang City. The hexahelix components in the development of the digital industry are government, academia, the business world, media, and financial institutions. Each component has its role in aligning common goals. Before establishing policies and implementing the Hexahelix concept, each stakeholder is expected to know their primary role, even though the implementation is carried out jointly and complements each other.